(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
The Fe-bearing intermetallic phases present in the as-cast AA6026 alloy and their evolution during homogenization treatments at 480-550°C were investigated using optical microscopy, SEM, and TEM techniques in combination with EDS analysis. In addition to the α-Al(Fe,Mn)Si phase with dendritic morphology, two types of plate-like Fe-bearing microconstituents were revealed in the microstructure of the as-cast alloy. The EDS microanalysis and electron diffraction showed that one set of platelets represented only thin sections of α-Al(Fe,Mn)Si microconstituent. The other set of plate-like microconstituents was identified as a tetragonal, silicon-rich δ-Al4(Fe,Mn)Si2 phase. The formation of the δ-Al4(Fe,Mn)Si2 phase was attributed to the chemical composition of the alloy. During homogenization, the metastable δ-Al4(Fe,Mn)Si2 transformed into the α-Al(Fe,Mn)Si phase and fragmented. The dendritic α-Al(Fe,Mn)Si microconstituents were also fragmented. However, while the α-Al(Fe,Mn)Si microconstituents preserved a b.c.c. crystal lattice throughout the process, the product of the transformation of the δ-Al4(Fe,Mn)Si2 phase exhibited primitive cubic lattice.